The role of principal leadership in improving the quality of learning in elementary school - Supriyono Supriyono; Happy Fitria; Alfroki Marta (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The leadership role of the principal in improving the quality of learning at SDN 3 Makarti Jaya, Banyuasin Regency can be said to have played a role in improving the quality of learning.As educators, school principals guide teachers how to deliver effective and efficient learning materials, as managers of principals able to optimize educational facilities, as administrators able to compile programs,as a supervisor able to compile an educational supervision program, as a headmaster leader Understand the condition of the school community, as an innovator able to implement reform (change for the better),as a motivator to be able to regulate the work / learning atmosphere, as an intreprenuer of the principal together with the school committee to work together to work creatively in extracting sources of empowerment to improve teacher professionalism,especially with regard to teachers to attend professionalism education and training as well as sending teachers to attend seminars.